The Opening and Closure of Oceanic Seaways During the Cenozoic: Pacemaker of Global Climate Change? - Karas, C (Geological Society of London, 2023)
The opening and constriction of oceanic gateways played an essential role in shaping the global climate throughout Earth’s history. In this review, we provide an overview of the best-documented feedbacks between gateway dynamics and climate change throughout the Cenozoic. The discussed tectonically induced events comprise: (i) the opening of the Tasmanian Gateway and the glaciation of Antarctica during the Eocene–Oligocene; (ii) the water-mass exchange between the Atlantic and the Mediterranean via the Strait of Gibraltar that has occurred since the Miocene; and (iii) the closure of the American Seaway and (iv) the constriction of the Indonesian Throughflow, both argued to have been instrumental in the intensification of Northern Hemisphere Glaciation during the late Pliocene and early Pleistocene. Lastly, we look at (v) the climatic impact of the flooding and submergence of the Bering Strait during the Plio-Pleistocene and its influence on the Atlantic Meridional Overturning Circulation. While different in their underlying mechanisms, geographical scale and temporal evolution, these case studies demonstrate that even seemingly small-scale changes in the configuration of ocean seaways fundamentally altered the global climate system via their impact on oceanic cur-rents, global heat transfer and carbon storage. © 2022 The Author(s).